The concept of significant damage in preventive environmental protection - Brkić Mladen N. (Glasnik Advokatske komore Vojvodine, 2019)
Significant damage as a substantive condition of a claim for the removal of a source of danger was not subjected to assessment in court proceedings. Although a prerequisite, the courts did not assess whether there was a threat of substantial harm in the particular cases. Considering that the Law on Environmental Protection is the basic law in the field of environmental protection, as lex specialis, it should be applied when assessing whether a particular source of danger presents a risk from which significant damage could occur. If there is a threat of significant harm in accordance with biological parameters, economic criteria should not be relevant in deciding whether to approve the request to remove the source of the hazard. In addition to the aforementioned general criterion, the court should consider whether the rules governing neighborhood relations are relevant between the claimant and the respondent. It is also important which area the source of danger is in, as well as which objects are endangered. Any influence beyond what is permissible will be considered relevant or significant.